2009
DOI: 10.1007/s11243-009-9276-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, DNA interaction studies and anticancer activity of platinum–clotrimazole complexes

Abstract: New trans-platinum complexes of clotrimazole (CTZ) have been prepared and characterized. Their interaction with DNA and activity against tumour cell lines were evaluated. [Pt (CTZ) 2 I 2 ] (1) was synthesized by the reaction of K 2 PtCl 4 , KI and CTZ, and [Pt(CTZ) 2 Cl 2 ] (2) by direct reaction of K 2 PtCl 4 with CTZ. These complexes were characterized by a combination of elemental analysis, molar conductivity, UV-Vis, IR, and NMR spectroscopy in one and two dimensions. DNA-platinum complex interactions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In the case of complex 5 , the presence of ethylenediamine ligand and the overall positive charge likely allow this compound to form hydrogen bonds with the bases of DNA and establish electrostatic interactions with the phosphate backbone. The weak interaction observed for the other compounds (data not shown), reminiscent of that described for NAMI (Gallori et al 2000), is likely due to electrostatic attraction/repulsion or minor groove binding, as previously reported for Pt-CTZ complexes (Navarro et al 2009). This is further supported by results of the Burton Assay on complexes 8 and 9 (Anzelloti, 2004), revealing 87 and 15 nmol/mg DNA of drug covalently bound to DNA after 48 h of incubation, respectively, much lower than was measured for complex 7 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the case of complex 5 , the presence of ethylenediamine ligand and the overall positive charge likely allow this compound to form hydrogen bonds with the bases of DNA and establish electrostatic interactions with the phosphate backbone. The weak interaction observed for the other compounds (data not shown), reminiscent of that described for NAMI (Gallori et al 2000), is likely due to electrostatic attraction/repulsion or minor groove binding, as previously reported for Pt-CTZ complexes (Navarro et al 2009). This is further supported by results of the Burton Assay on complexes 8 and 9 (Anzelloti, 2004), revealing 87 and 15 nmol/mg DNA of drug covalently bound to DNA after 48 h of incubation, respectively, much lower than was measured for complex 7 .…”
Section: Resultssupporting
confidence: 78%
“…Some of us reported that Ru(KTZ) 2 Cl 2 induces cytotoxicity and apoptosis-associated caspase-3 activation in several cancer cell lines including C8161 melanoma and HT-29 colon carcinoma, irrespective of p53 status, with IC 50 values around 25 μM; this complex targets the mitochondria and is more effective than KTZ, CTZ, Ru(CTZ) 2 Cl 2 , or cisplatin at inducing PARP fragmentation and proapoptotic Bak expression (Strasberg et al 2004). Pt(CTZ) 2 Cl 2 was found to be active against a panel of human tumor cell lines, including prostate, pancreas, breast, and colon, while the Pd analogue was inactive (Navarro et al 2009; Navarro et al 2006). We recently reported that the arene-Ru-CTZ and arene-Ru-KTZ compounds 1 – 12 (Figure 2) display high activity against Leishmania major and Trypanosoma cruzi with very low toxicity to normal mammalian cells (Iniguez et al 2013; Martinez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research discovered that 2‐phenylpyridine complex could be easily dissociated in the biological systems, which was favorable for reducing side effects and cell resistance. However, organoplatinum(II) imidazole 48 showed weak anticancer effects toward Jurkat leukemia and Raji cell lines with IC 50 values of 12 and 14 μg/mL, respectively, in comparison with cisplatin (IC 50 = 9.9 and 9.0 μg/mL) . This work presents some points for the development of more potent organometallic anticancer complexes compatible with biological systems.…”
Section: Imidazoles As Anticancer Agentsmentioning
confidence: 82%
“…Indeed, several other metal–clotrimazole complexes, such as ruthenium–clotrimazole and platinum–clotrimazole, also display promising antineoplastic characteristics (Navarro et al . ; Robles‐Escajeda et al . ).…”
Section: Discussionmentioning
confidence: 99%